2017
DOI: 10.3892/or.2017.5611
|View full text |Cite
|
Sign up to set email alerts
|

miR-944 inhibits cell migration and invasion by targeting MACC1 in colorectal cancer

Abstract: Dysfunction of microRNAs (miRNAs) is strongly proved to participate in the pathogenesis and tumorigenicity of colorectal cancer (CRC). miR-944 was reported to play either oncogenic or tumor suppressive roles in human cancers. A recent study reported that the levels of miR-944 in recurrent CRC patients were evidently lower than that in non-recurrent cases, suggesting that miR-944 may function as a tumor suppressive miRNA in CRC. Yet, the clinical value and biological function of miR-944 remain rarely known in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 24 publications
2
43
0
Order By: Relevance
“…Although there are many studies on microRNA and colon cancer, such as mir-30a-5p (miR-30a) regulates cell motility and EMT by targeting TM4SF1 in colorectal cancer [18]. MiR-944 inhibits cell migration and invasion by targeting MACC1 in colorectal cancer [19]. At present, the study of miR-483 and colon cancer is relatively rare.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many studies on microRNA and colon cancer, such as mir-30a-5p (miR-30a) regulates cell motility and EMT by targeting TM4SF1 in colorectal cancer [18]. MiR-944 inhibits cell migration and invasion by targeting MACC1 in colorectal cancer [19]. At present, the study of miR-483 and colon cancer is relatively rare.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four studies demonstrated the downregulation of twenty-five miRs associated with advanced TNM stage: miR-302c 67 , miR-466 68 , miR-340 69 , miR-196b-5p 70 , miR-944 71 , miR-30d 72 , miR-22 50 , miR-296 73 , miR-384 74 , miR-199b 48 , miR-128 75 , miR-33b 76 , miR-155-5p 77 , miR-154 78 , miR-149 79 , miR-194 80 , miR-133b 37 , miR-15a 34 , miR-100 81 , miR-133a 41 , miR-335 82 , miR-378a-3p 58 , miR-378a-5p 58 , miR-218 83 and miR-16 34 . Two studies demonstrated the upregulation of miR-182 43, 44 associated with advanced TNM stage and others 22 studies pointed 23 different upregulated miRs associated with advanced TNM stage.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 32 studies demonstrated the association between the downregulation of 32 miRs and the presence of lymph node metastasis such as miR-6852 106 , miR-302c 67 , miR-466 68 , miR-340 69 , miR-944 71 , miR-30d 72 , miR-22 50 , miR-296 73 , miR-199b 47 , let-7a-5p 98 , miR-132 99 , miR-497 107 , miR-206 100 , miR-128 75 , miR-154 78 , miR-149 79 , miR-24-3p 54 , miR-15a 34 , miR-16 34, 36 , miR-193a-5p 108 , miR-100 81 , miR-133a 41 , miR-205 109 , miR-335 82 , miR-378 101 , miR-218 83 , miR-138 110 , miR-625 111 , miR-212 112 , miR-195 113 , miR-133b 37 and miR-30c 103 . Other 30 studies verified the upregulation of miR-1296 84 , miR-200c 114 , miR-21 26, 29 , miR-130a 85 , miR-7 55 , miR-96 86 , miR-1260b 115 , miR-517a 87 , miR-106b 88 , miR-320e 89 , miR-196a 57 , miR-196b 57 , miR-376a 116 , miR-720 91 , miR-494 61 , miR-630 92 , miR-181a 31 , miR-20a 62 , miR-210 93 , miR-182 43, 44 , miR-25 94 , miR-191 95 , miR-183 46 , miR-199a-3p 117 , miR-429 105 , miR-92a 96 , miR-10b 118 , miR-155 30 and miR-552 97 associated with the presence of lymph node metastasis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…hsa-mir-10b, the feature with the highest S f score, while not appearing in the surveys, 165 is currently under clinical trials as oncomarker for Glioma [45], and it is mentioned in a 166 recent article as possible oncomarker [46]. hsa-mir-944 at the moment is known to decrease malignant features in 170 gastric [49], colorectal [50] and endometrial [51] cancers. hsa-mir-9-1, hsa-mir9-2, and hsa-mir9-3, generate the oncogenic 169 hsa-mir-9 [48].…”
mentioning
confidence: 99%